PENGARUH RESIKO KREDIT, KECUKUPAN MODAL, HUTANG, DAN PENDAPATAN BUNGA TERHADAP PROFITABILITAS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sinabang, Boniara; Sembiring, Sabeth (UNIKA Santo Thomas, 2020)
This study aims to examine the effect of credit risk as measured by non-performing loans, the level of capital adequacy as measured by a capital adequacy ratio, debt as measured by debt to equity ratio, and interest income as measured by net interst margins on the level of profitability as measured by returns on assets in banking companies listed on the Indonesia Stock Exchange (IDX). This research is classified as causative research. The population in this study were all banking companies listed on the Indonesia Stock Exchange in 2011 to 2015. While the sample of this study was determined by purposive sampling method so that 24 sample companies were obtained. The type of data used was secondary data obtained from www.idx.co.id. The analytical method used is multiple regression analysis with a significance level of 5%. The partial test results show that credit and debt risk have a negative and significant effect on profitability, capital adequacy has no effect on profitability, interest income has a positive and significant effect on profitability. Simultaneous test results show that credit risk, capital adequacy, debt, and interest income affect profitability. Therefore, banks consider the factors of credit risk, capital adequacy, debt and interest income in the context of achieving the expected level of profit by paying attention to the quality of credit distribution, cultivate capital well and use capital effectively, debt that is made into productive assets is well managed, as well as maintaining loan interest rates offered so as to generate high capital.